Intestinal fatty acid binding protein is associated with cardiac function and gut dysbiosis in chronic heart failure - Nendl, Andraž; Raju, Sajan C.; Broch, Kaspar; Mayerhofer, Cristiane C. K.; Holm, Kristian; Halvorsen, Bente; Lappegård, Knut Tore; Moscavitch, Samuel; Hov, Johannes Roksund; Seljeflot, Ingebjørg; Trøseid, Marius; Awoyemi, Ayodeji (Frontiers in Cardiovascular Medicine, 2023)
Background: The gut microbiota in patients with chronic heart failure (HF) is characterized by low bacterial diversity and reduced ability to synthesize beneficial metabolites. These changes may facilitate leakage of whole bacteria or bacterial products from the gut into the bloodstream, which may activate the innate immune system and contribute to the low-grade inflammation seen in HF. In this exploratory cross-sectional study, we aimed to investigate relationships between gut microbiota diversity, markers of gut barrier dysfunction, inflammatory markers, and cardiac function in chronic HF patients. Methods: In total, 151 adult patients with stable HF and left ventricular ejection fraction (LVEF)<40% were enrolled. We measured lipopolysaccharide (LPS), LPS-binding protein (LBP), intestinal fatty acid binding protein (I-FABP), and soluble cluster of differentiation 14 (sCD14) as markers of gut barrier dysfunction. N-terminal pro-B-type natriuretic peptide (NT-proBNP) level above median was used as a marker of severe HF. LVEF was measured by 2D-echocardiography. Stool samples were sequenced using 16S ribosomal RNA gene amplification. Shannon diversity index was used as a measure of microbiota diversity. Results: Patients with severe HF (NT-proBNP>895 pg/mL) had increased I-FABP (p<0.001) and LBP (p=0.03) levels. ROC analysis for I-FABP yielded an AUC of 0.70 (95% CI 0.61-0.79, p<0.001) for predicting severe HF. A multivariate logistic regression model showed increasing I-FABP levels across quartiles of NT-proBNP (OR 2.27, 95% CI 1.42-3.62, p=0.001). I-FABP was negatively correlated with Shannon diversity index (rho=-0.30, p=<0.001), and the bacterial genera Ruminococcus gauvreauii group, Bifidobacterium, Clostridium sensu stricto, and Parasutterella, which were depleted in patients with severe HF. Conclusions: In patients with HF, I-FABP, a marker of enterocyte damage, is associated with heart failure severity and low microbial diversity as part of an altered gut microbiota composition. I-FABP may reflect dysbiosis and may be a marker of gut involvement in patients with HF.